(untitled) (Research, Society and Development, 2023)
Surgical removal of impacted mandibular third molars whose dental roots are close to the inferior alveolar nerve canal (IAN) represents a high-risk procedure for the development of injury in this anatomical structure. IAN injury is a rare, often serious complication that can occur as a result of mandibular third molar extraction. Its incidence is viable from 0.5% to 8%, but it can increase to 20 to 50% when the roots make contact with the cortical bone of the inferior alveolar nerve. The coronectomy technique has been proposed as an alternative to the complete removal of a third molar impacted inferior located next to the NAI. The technique consists of removing only the crown of the tooth, leaving the root in the alveolus, theoretically avoiding direct or indirect damage to the NAI. This work proposes to carry out a narrative review of the literature, seeking to discuss the effectiveness of coronectomy in relation to sensory disorders, when removing impacted lower third molars and unfavorably positioned in relation to the inferior alveolar nerve. Evidences on the long-term results of coronectomy allow us to state that it is a safe and effective method in cases where the lower third molar is in a position at high risk of complications involving the IAN.